Endoscopic Physeal Bar Resection Combined with Guided Growth using Local Fat Graft Interposition and Post-Operative CT Assessment for the Treatment of Genu Valgus : a case report - Mohd Anuar Ramdhan, Ibrahim; Faris Indra Prahasta, Didi Indra (Dow University of Health Sciences., 2022)
Distal femur physeal arrest due to physeal bar formation with progressive deformities is an unwanted complication following injury to the femur. Various techniques of physeal bar resection, either using open techniques or endoscopic methods, have been described in the available literature. The associated angular deformities could be addressed either with osteotomy in acute correction or gradual correction with an external fixator or guided growth principle. We would like to recommend the use of fat tissues from the surgical wound used for the guided growth and evaluation of the recurrence of the physeal bar via computed tomography in our case. To our knowledge there is no previous reports using similar approach. We shall share case of a severely comminuted distal femoral physeal injury Salter-Harris IV complicated with central physeal bar causing growth disturbance and angular knee deformity treated via endoscopic resection surgery and simultaneous 8-plate insertion for which has shown a good radiological and functional outcome.